The Other Side of Abortion : The Doctor-Writer in Martin Winckler's La Vacation (1989) - Cenedese, Marta-Laura (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
In 1989, physician and author Martin Winckler published his first novel, La vacation, in which he introduced the fictional medical practitioner Bruno Sachs. In the novel, the author focuses on Bruno's moves and gestures, his thoughts and feelings as he performs abortions in a French public clinic. In this article I argue that the novel is a complex, metanarrative account of a medical gesture that engenders and reveals conflicting (and conflictual) situations, emotions and experiences. I suggest that through an elaborate narrative form La Vacation foregrounds the 'sticky' feelings surrounding abortion-that abortionist doctors are deeply touched and taxed by the procedure, as convinced as they might be of its importance and rightfulness. Making reference to further works by Winckler, such as La maladie de Sachs and Les trois medecins, this article analyses how the novel's form is crucial to address the complexity of the affective experience. I will show how Winckler's novel problematises the subjects and objects of abortion and I will argue that, in his first literary work, he is inscribing himself into a lineage of doctor-writers who are also activist writers who use their pens as swords.